1989
DOI: 10.1002/jcc.540100702
|View full text |Cite
|
Sign up to set email alerts
|

Steric effects on reaction rates. XI. Solvolysis of tertiary carbon substrates rationalized by molecular mechanics calculations

Abstract: The steric energy difference (Est) between tertiary carbenium ions (R+) and the corresponding alcohols has been calculated by MM2 for a series of tertiary nonbridgehead substrates and correlated with their rate of solvolytic reactivity. Satisfactory correlation is obtained, except for p-nitrobenzoates of highly congested substrates. The slope and intercept of the correlations remain almost unchanged if bridge-head substrates are included in the plot. However, the quality of the fit is better for bridgehead sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…2,4 In addition, the tertiary neopentyl derivative 5, which should be far less subject to nucleophilic solvent assistance, 13,14 solvolyses also at an enhanced rate, although the deviation is much less pronounced than in the case of tert-butyl (9). The rate ratio for solvolysis of 1-adamantyl vs. tert-butyl (2-methyl-2-propyl) derivatives varies from ca 1:5000 in EtOH 10 to 1600 in MeOH 11 and 1:2.4 12 in 97% aqueous HFIP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4 In addition, the tertiary neopentyl derivative 5, which should be far less subject to nucleophilic solvent assistance, 13,14 solvolyses also at an enhanced rate, although the deviation is much less pronounced than in the case of tert-butyl (9). The rate ratio for solvolysis of 1-adamantyl vs. tert-butyl (2-methyl-2-propyl) derivatives varies from ca 1:5000 in EtOH 10 to 1600 in MeOH 11 and 1:2.4 12 in 97% aqueous HFIP.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, since the calculations were empirical, and since the forcefields used were adjusted such as to provide an optimum correlation with the experimental data, the significance of the calculations is questionable. Early empirical force-field calculations have been used to rationalize the structural effects on the rate constants of solvolysis in terms of strain changes between the bridgehead compound and the developing carbenium ion, which was assumed to be close to the transition state of the reaction in terms of energy and structure.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that all of the rate constants established by Bentley could be accommodated with the calculated strain changes by means of a single correlation [7]. Tertiary derivatives of general structure, such as acyclic, mono-, and polycyclic compounds fit the same correlation, although the quality of the plot is significantly below that observed for the bridgehead derivatives alone [8].…”
mentioning
confidence: 99%
“…A series of 24 bridgehead or rigid tertiary bridgehead derivatives evenly distributed over the entire rate range was selected, and the steric energy difference dE,,(R+ -RBr) was calculated with the UNICAT 4 carbenium ion force field [7] (cf. Appendix) and correlated with the solvolytic reactivity under standard conditions [4] [5] [8] by means of Eqn. I :…”
mentioning
confidence: 99%